IMPLEMENTASI KURIKULUM TAHFIDHUL QUR'AN - SITI NASIROH; Siti Anisatun Nafi'ah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2022)
In educational units, the curriculum is an educational design that is used as a reference for educational units to carry out an education. Curriculum and education are inseparable from each other. Because in an educational unit, it must have a design or curriculum. In this study, we will discuss the implementation of the local content curriculum Tahfidzul Qur'an. This research was conducted at MI Imam Puro Sutoragan. This type of research is a qualitative research that describes how the implementation of the local content curriculum Tahfidzul Qur'an at MI Imam Puro Sutoragan. The technique of collecting data was done by interviewing the head of the Madrasah, the deputy head of the curriculum section, the subject teacher and two student representatives from class VI. From the results of the study, it was found that MI Imam Sutoragan began implementing the local content curriculum of tahfidzul Qur'an in the 2019/2020 school year. The target of implementing the Tahfidzul Qur'an curriculum is that all MI Imam Puro Sutoragan graduates have a minimum of 30 chapters of memorization.